Die Stellung der Frau in der afghanischen Verfassungsordnung im Spannungsverhältnis zwischen islamischem Recht und Völkerrecht - unter besonderer Berücksichtigung des Scheidungsrechts - Aryobsei, Mina (Universitätsverlag Göttingen, 2014)
After the fall of the Taliban, the new Afghan constitution of 2004 marks a fundamental beginning for the status of women - at least from a normative perspective. Art. 22 of the Afghan constitution contains: "The citizens of Afghanistan, man and woman, have equal rights and duties before the law." According to Art. 7 of the constitution the state shall observe i. a. the international treaties to which Afghanistan has joined. This also covers the Convention on the Elimination of All Forms of Discrimination against Women. At the same time, Art. 3 of the constitution provides that no law should contravene the tenets and provisions of the holy religion of Islam in Afghanistan. But how do these different sources of law interact in conflicting legal fields? There are no exiting provisions of the constitution explicitly offering an answer to this problem. This work focuses on the solution of this question regarding the status of women, especially in the law of divorce.